1996
DOI: 10.1113/expphysiol.1996.sp003941
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a sodium‐dependent magnesium efflux from magnesium‐loaded rat pancreatic acinar cells

Abstract: SUMMARYThis study investigates the mechanism of magnesium (Mg2") transport (efflux) from the exocrine rat pancreas. Permeabilized pancreatic acini were loaded with Mg2+ by employing a high-Mg2+ (12 mM) buffer containing A23 187 (6 /LM). Net Mg2+ efflux was measured using the technique of atomic absorbance spectrophotometry. Incubation of preloaded acini in a buffer deficient in Mg2+ resulted in a large and time-dependent release of Mg2+ with maximal efflux occurring within 40 min. Pretreatment of loaded acini … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Our present results further confirm previous findings which suggest that Mg 2+ -loaded, Ca 2+ -depleted thymocytes display Na + /Mg 2+ exchangers with different stoichiometries (18). In these studies the Na + /Mg 2+ exchange detected by Magfura-2 fluorescence required the use of Ca 2+ -depleted cells because Ca 2+ , at nanomolar concentration, masks milimolar changes in Mg 2+ (31)(32)(33)(34)(35). It is possible that cytosolic Ca 2+ may have a regulatory role on Na + /Mg 2+ exchangers, perhaps through phosphorylative processes.…”
Section: Physiological Roles Of Ping Pong and Simultaneous Na + /Mg 2...supporting
confidence: 92%
“…Our present results further confirm previous findings which suggest that Mg 2+ -loaded, Ca 2+ -depleted thymocytes display Na + /Mg 2+ exchangers with different stoichiometries (18). In these studies the Na + /Mg 2+ exchange detected by Magfura-2 fluorescence required the use of Ca 2+ -depleted cells because Ca 2+ , at nanomolar concentration, masks milimolar changes in Mg 2+ (31)(32)(33)(34)(35). It is possible that cytosolic Ca 2+ may have a regulatory role on Na + /Mg 2+ exchangers, perhaps through phosphorylative processes.…”
Section: Physiological Roles Of Ping Pong and Simultaneous Na + /Mg 2...supporting
confidence: 92%
“…We could further rule out the involvement of a sodium-magnesium exchanger, although it has been suggested that this antiporter is involved in magnesium movements across the membrane of pancreatic acinar cells (53,54). Those experiments, however, were done in the absence of a calcium chelator, and the perfusion of acinar cells with sodium-deficient medium resulted in a large increase of intracellular calcium via action of the Na ϩ /Ca 2ϩ exchanger.…”
Section: Discussionmentioning
confidence: 99%
“…27 28 Accordingly, incubating Mg -loaded rat pancreatic acinar cells in a local anaesthetic (lidocaine) strongly reduced the Mg 2+ efflux with respect to controls. 29 The Na + CSF concentration remained unchanged because hydrated Na + , the main osmolyte in the organism, shifts between compartments retaining water, thus without altering its concentration. Alternatively, and less likely, considering that local anaesthetics inhibit not only Na + channels but also various K + channels 30 and Ca 2+ channels, 31 levobupivacaine at very low doses might have inhibited Mg 2+ active transport at the choroid plexus.…”
Section: Data Analysed N=16mentioning
confidence: 99%